Azasydnone – novel "green" building block for designing high energetic compounds. Issue 38 (21st September 2018) - Dalinger, Igor L.; Serushkina, Olga V.; Muravyev, Nikita V.; Meerov, Dmitry B.; Miroshnichenko, Evgeniy A.; Kon'kova, Tatyana S.; Suponitsky, Kyrill Yu.; Vener, Mikhail V.; Sheremetev, Aleksei B.
Abstract : The azasydnone unit is a promising explosophoric block for future generations of highly thermostable and dense energetic materials. Abstract : The discovery of novel explosophoric building blocks for the construction of energetic compounds is extremely rare. Here, based on the comparative experimental properties and computational analysis of compounds where nitroaryl backbones were bonded with various nitrogen/oxygen-rich groups, it is shown that compounds having the azasydnone group possess higher density, detonation performance and thermal stability than their corresponding nitro, azido and tetrazole-analogs. All of these properties, as well as the oxygen balanced content of the "green" nitrogen rich endothermic unit make them an attractive explosophoric building block in the field of energetic materials chemistry.